Systemic Regulation of Iron Acquisition by Arabidopsis in Environments with Heterogeneous Iron Distributions. (21st April 2022) - Tabata, Ryo; Kamiya, Takehiro; Imoto, Shunpei; Tamura, Hana; Ikuta, Kumiko; Tabata, Michika; Hirayama, Tasuku; Tsukagoshi, Hironaka; Tanoi, Keitaro; Suzuki, Takamasa; Hachiya, Takushi; Sakakibara, Hitoshi
Abstract: Nutrient distribution within the soil is generally heterogeneous. Plants, therefore, have evolved sophisticated systemic processes enabling them to optimize their nutrient acquisition efficiency. By organ-to-organ communication in Arabidopsis thaliana, for instance, iron (Fe) starvation in one part of a root drives the upregulation of a high-affinity Fe-uptake system in other root regions surrounded by sufficient levels of Fe. This compensatory response through Fe-starvation-triggered organ-to-organ communication includes the upregulation of Iron-regulated transporter 1 ( IRT1 ) gene expression on the Fe-sufficient side of the root; however, the molecular basis underlying this long-distance signaling remains unclear. Here, we analyzed gene expression by RNA-seq analysis of Fe-starved split-root cultures. Genome-wide expression analysis showed that localized Fe depletion in roots upregulated several genes involved in Fe uptake and signaling, such as IRT1, in a distant part of the root exposed to Fe-sufficient conditions. This result indicates that long-distance signaling for Fe demand alters the expression of a subset of genes responsible for Fe uptake and coumarin biosynthesis to maintain a level of Fe acquisition sufficient for the entire plant. Loss of IRON MAN / FE - UPTAKE - INDUCING PEPTIDE ( IMA / FEP ) leads to the disruption of compensatory upregulation of IRT1 in the root surrounded by sufficient Fe. In addition, our split-root culture-based analysis provides evidence that the IMA3/FEP1-MYB10/72 pathway mediates long-distance signaling in Fe homeostasis through the regulation of coumarin biosynthesis. These data suggest that the signaling of IMA/FEP, a ubiquitous family of metal-binding peptides, is critical for organ-to-organ communication in response to Fe starvation under heterogeneous Fe conditions in the surrounding environment.